Comparison of plant nutrient contents in vermicompost from selected plant residues - Yan, Yi Wei; Abd Aziz, Nor Azwady; Shamsuddin, Zulkifli; Mustafa, Muskhazli; Abd. Aziz, Suraini; Teng, Suk Kuan (Academic Journals, 2013)
In this experiment, earthworm, Eudrilus eugeniae was fed with different plant residues: grass clippings, sago waste and rice straw. These organic wastes were also left to decompose naturally as the control. Analysis on samples vermicompost showed that humic acid content was highest in rice straw, followed by grass clippings compared to those of sago wastes. Total phosphorus (P) was lower in vermicomposts as compared to the controls, however, highest extractable P was found in rice straw vermicompost (0.33 ± 0.00 g/kg). Sago waste vermicompost (22.79 ± 0.01 g/kg) contained highest total calcuim (Ca) compared to the grass clippings (1.39 ± 0.01 g/kg) and rice straw (8.22 ± 0.06 g/kg) vermicompost. Significant positive correlations between nutrient contents in raw plant residues and vermicompost were observed for total nitrogen (N) (r = 0.779), potassium (K) (r = 0.998) and Ca (r = 0.997). The study showed that nutrient in initial wastes material affects the nutrient contents of vermicompost. This research suggested that among the plant residues studied, vermicomposting of rice straw produced vermicompost with the highest plant extractable nutrient contents.